Textural Analysis, Erodibility Index Analysis and Hydro Network Pattern Delineation of Eocene Strata, South-Eastern Nigeria (Global Journal of Science Frontier Research, 2018)
Detailed field based studies were carried out on Eocene Strata of Nanka Sandstone, unit of Niger Delta. Textural analyses were carried out on twenty-one samples of the rock collected from various units across the study area. Gradistat v.8.0 was used to analyze the data obtained for sieve analysis. TRI-PLOT v. 1-4-2 was used to analyze the data obtained for pebble morphometry. The sieve analysis data were also subjected to the Erodibility Index Analysis (EIA) to estimate Erodibility Tendency (ET). By manual delineation, and the use of ArcGIS, the Hydro Network Pattern (HNP) was carried out. A reflection of a predominant shallow marine depositional environment controlled by tidal influence with its corresponding stratigraphy was observed. Very severe Erodibility Tendency (ET) was predicted based on very high values of Soil Loss (R) through the calculated erodibility indices, direct heavy raindrop impact on the sediments and the Hydro Network Pattern (HNP) which favor intense erosion of the study area. The criticality of this intense accelerated erosion is being factored by the friability and very high sand to clay ratio of Nanka Formation.
Keywords: eocene strata; nanka sandstone; niger delta; textural analyses; erodibility index analysis (EIA); erodibility tendency (ET); hydro network pattern (HN